A study of the communication-related variables that contribute to the job retention of call center agent the case of eTelecare - Jamandre, Niel Kenneth F. (College of Arts and Letters, University of the Philippines Diliman, 2008)
The call center industry is a component of Business Process Outsourcing (BPO) which functions by outsourcing services in order to lower operational costs. However, the Philippine BPO industry experiences a 30% call center agent turnover rate. This research sought to identify and analyze the communication-related variables that contribute to the retention of call center agents in eTelecare. Specifically, it aimed to describe the processes of recruitment, qualifications of applicants, selection, hiring, orientation, training, and nature of work of call center agents. this study also sought to identify communication variables that can serve as predictors to job retention of call center agents in eTelecare.